Eksperimen pembelajaran matematika dengan strategi problem based learning dan numbered heads together terhadap hasil belajar ditinjau dari keaktifan siswa(penelitian eksperimen kelas vii semester genap di mts negeri surakarta ii tahun ajaran 2015/2016) - Nurma Wati, Dea (2016)
Dea Nurma Wati / A 410 120 009. Experiments with Strategy Learning Problem Based Learning and Number Heads Together Against Learning Outcomes In terms of active participation by students. Essay. Faculty of Teacher Training and Education. Muhammadiyah University of Surakarta. March 2016. The background of this study is the low result of learning mathematics in MTsN Surakarta II. The cause may come from within the students that the students' motivation and of the external factors, namely learning methods applied by teachers. The aim of research to describe and analyze: (1) the influence of mathematics learning with PBL and NHT based on the results of learning mathematics, (2) the effect on the students 'active learning outcomes, (3) the interaction between students' active learning strategies and learning outcomes. This research is a quasi experimental with experimental design. The study population was all students of class VII MTs N 2 Surakarta class the first semester of the 2015/2016 academic year. The study sample consisted of two classes. The sampling technique using cluster random sampling. The test method usage data collection and documentation. Data were analyzed by analysis of variance with two different cell lines. The results of the data analysis with a significance level of 5% was obtained: (1) there is the influence of PBL and NHT the learning outcomes of mathematics, with FA = 5,027 (2) no influence activity of students for learning outcomes, with FB = 11234 (3) there is no interaction between PBL and student activity NHT with the learning outcomes, with FAB = 0.016.